The Effect of Food Quality and Price on Customer Satisfaction at Doubletree Hotel Room Service by Hilton Jakarta-Diponegoro - Edvin Fairliantina; Aldo Arifin Pringga Utama; Hajar Adhayanti (Jurnal Info Sains : Informatika dan Sains, 2025)
Room service is one of the superior services offered by starred hotels, including the DoubleTree by Hilton Jakarta-Diponegoro Hotel. Although generally well-rated, this hotel's room service has experienced complaints regarding the quality of the food served and the price that some customers consider inappropriate. This problem raises questions about the extent to which the quality of food products and prices can affect the level of customer satisfaction. This study aims to analyze the effect of food product quality and price on customer satisfaction in room service at the DoubleTree by Hilton Jakarta-Diponegoro Hotel. The method used is quantitative with a descriptive and associative approach. Data were collected by distributing questionnaires to customers. The results of the study indicate that the quality of food products and prices partially and simultaneously have a positive and significant effect on customer satisfaction. Good food quality and prices that meet customer expectations are key factors in shaping positive perceptions of room service. This research is expected to provide evaluation material for hotels to improve the quality and value of their products to meet customer expectations.